Phase stability, electronic and local structures of Li-doped (K,Na)NbO3 under hydrostatic pressure from first principles calculation - Metta P. (2023)
Despite the promising potential to replace Pb-based ferroelectric materials, potassium sodium niobate-based ceramics retain one critical drawback, namely, the temperature sensitivity which is considered the most challenging in practical applications. It has been proposed that the formation of a phase boundary rhombohedral–tetragonal (R–T) can stabilize the temperature dependence of this material. External factors such as thermal, electrical, magnetic and mechanical fields can induce structural phase transition and influence the piezoelectric and ferroelectric responses. In this study, the electronic and local structures of (Li,Na,K)NbO3 (KNLN) under hydrostatic pressure were investigated using first principles calculations within the generalized-gradient approximation. It is revealed that the internal stress presented in the KNLN ceramic due to the ionic size difference among the A-cation favors the formation of the tetragonal phase in ambient conditions. When the material is subjected to external pressure, the denser orthorhombic phase is more preferable at around 5.85 GPa and the rhombohedral phase at around 7.20 GPa. The bond strength and bandgap decrease, because the electronic charge density and electronic interaction are amplified. In addition, we observed the octahedral rotation signifying the lattice distortion for the tetragonal phase, while the inter-plane tilting takes over in other phases at high pressure.